Pathology and Pathogenesis of Lassa Fever: Novel Immunohistochemical Findings in Fatal Cases and Clinico-pathologic Correlation. (31st August 2021) - Shieh, Wun-Ju; Demby, Austin; Jones, Tara; Goldsmith, Cynthia S; Rollin, Pierre E; Ksiazek, Thomas G; Peters, Clarence J; Zaki, Sherif R
Abstract: Background: Lassa fever is a zoonotic, acute viral illness first identified in Nigeria in 1969. An estimate shows that the "at risk" seronegative population (in Sierra Leone, Guinea, and Nigeria) may be as high as 59 million, with an annual incidence of all illnesses of 3 million, and fatalities up to 67 000, demonstrating the serious impact of the disease on the region and global health. Methods: Histopathologic evaluation, immunohistochemical assay, and electron microscopic examination were performed on postmortem tissue samples from 12 confirmed Lassa fever cases. Results: Lassa fever virus antigens and viral particles were observed in multiple organ systems and cells, including cells in the mononuclear phagocytic system and other specialized cells where it had not been described previously. Conclusions: The immunolocalization of Lassa fever virus antigens in fatal cases provides novel insightful information with clinical and pathogenetic implications. The extensive involvement of the mononuclear phagocytic system, including tissue macrophages and endothelial cells, suggests participation of inflammatory mediators from this lineage with the resulting vascular dilatation and increasing permeability. Other findings indicate the pathogenesis of Lassa fever is multifactorial and additional studies are needed. Abstract : Lassa hemorrhagic fever remains a worldwide public health concern. We describe novel immunohistochemical findings with clinico-pathologic correlation of Lassa virus infection in fatal human cases. Viral antigen was detected in multiple organ systems where it had not been reported previously.